Dielectric properties of the chitosan – spinel CoFe2O4 composites. (3rd October 2018) - Markiewicz, E.; Chybczyńska, K.; Grząbka-Zasadzińska, A.; Borysiak, S.; Wolak, J.; Matczak, M.
ABSTRACT: The composite material made of biodegradable chitosan as a matrix and spinel CoFe2 O4, exhibiting the ferrimagnetic properties, was proposed to be suitable for application in modern transducers, for instance in a loudspeaker without a permanent magnet. The spinel was obtained by high-energy ball milling followed by annealing. The composites were prepared by the solvent casting method. The dielectric studies using broadband impedance spectrometer and the applied methodology of subtracting the conductivity term from the dielectric absorption spectra pointed to the presence of two low-frequency relaxations in chitosan as well as in the composites: α – related to the glass transition (310–350 K), and σ – related to the migration of protons (350–420 K). In the high frequency range, the secondary β -relaxation, related to side group motions by means of the glucosidic linkage, was observed in the temperature range 300–350 K. However, for the composite samples, additionally, the process associated with the migration of oxygen vacations in the spinel grains was detected within the temperature range 350–380 K. One can notice a significant decrease in the activation energy of all processes with increasing contents of spinels in the chitosan matrix.